Detection and mitigation security threats in cloud systems - Ayitey, Addy Andrene Nii (2021)
A thesis presented to the Department of Computer Science, Kwame Nkrumah University of Science and Technology, in partial fulfillment of the requirement of Master of Science (Information Technology).